2014
DOI: 10.1080/15564886.2013.845124
|View full text |Cite
|
Sign up to set email alerts
|

How Victim and Execution Impact Statements Affect Mock Jurors’ Perceptions, Emotions, and Verdicts

Abstract: This study examines the effects of Victim Impact Statements (VISs) and Execution Impact Statements (EISs) on death-qualified mock jurors through a 2 (VIS/no VIS) by 2 (EIS/no EIS) between-subjects design in which participants read a capital murder trial and completed an online survey. The VIS and EIS had no effect on verdicts, but the VIS increased participants' negative emotions as well as perceptions of the victim and those who gave impact statements. Conversely, the EIS increased positive emotions and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Butler (2008) found that in a sample of 200 venire-persons given a summary of a capital case including the penalty phase, the presence of VIS did not lead to significantly more death penalty judgments. More recent studies by Boppre and Miller (2015) and Wevodau, Cramer, Kehn, and Clark (2014) did not find that VIS affected sentencing. The inconsistencies in findings suggest that other, moderating influences are at work.…”
Section: The Impact Of Angry Versus Sad Victim Impact Statements (Vismentioning
confidence: 76%
See 2 more Smart Citations
“…Butler (2008) found that in a sample of 200 venire-persons given a summary of a capital case including the penalty phase, the presence of VIS did not lead to significantly more death penalty judgments. More recent studies by Boppre and Miller (2015) and Wevodau, Cramer, Kehn, and Clark (2014) did not find that VIS affected sentencing. The inconsistencies in findings suggest that other, moderating influences are at work.…”
Section: The Impact Of Angry Versus Sad Victim Impact Statements (Vismentioning
confidence: 76%
“…Studies cited earlier that have found significant effects of VIS on decision making may have used VIS that elicited primarily anger in their participants. As we noted, much of the research on VIS and emotions have failed to separate out the negative emotions of anger and sadness or produce clear evidence of angry responses in jurors (e.g., Boppre & Miller, 2015;Myers et al, 2002;Platania & Berman, 2006;Wevodau et al, 2014). One exception is the study conducted by Paternoster and Deise (2011), who found that anger mediated the effects of a VIS on death sentences.…”
Section: Vismentioning
confidence: 89%
See 1 more Smart Citation
“…Past research strongly supports the assertion that emotions can impact juror decision-making (e.g., Georges, Wiener, & Keller, 2013;Semmler et al, 2002). A great deal of existing literature regarding emotions and juror decision-making has focused on the effects of victim impact statements and emotional evidence (e.g., Boppre & Miller, 2014;Matsuo & Itoh, 2016;Wevodau et al, 2014) as well as on the impact of the demeanour of defendants, witnesses, and victims (e.g., Golding, Fryman, Marsil, & Yozwiak, 2003;Pryor & Buchanan, 1984). A number of studies have also examined mock jurors' emotional responses to gruesome evidence (e.g., Bright & Goodman-Delahunty, 2004;Bright & Goodman-Delahunty, 2006;Douglas, Lyon, & Ogloff, 1997).…”
Section: Emotions and Crime Seriousnessmentioning
confidence: 77%
“…Moreover, posttraumatic stress symptoms and more time since victimization were positively correlated with a higher likelihood of VIS submission (Lens et al, 2013). Victims may submit impact statements for many reasons including to obtain catharsis, to have a voice in the system, or to influence sentencing (Boppre & Miller, 2014;Gordon & Brodsky, 2007;Roberts & Edgar, 2006).…”
Section: Factors Related To Vissmentioning
confidence: 99%